2020
DOI: 10.3390/catal10020209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zirconia on Hydrothermally Synthesized Co3O4/TiO2 Catalyst for NOx Reduction from Engine Emissions

Abstract: Effect of zirconia on the 6 wt.% Co3O4/TiO2 catalyst for NOx reduction is investigated in this paper. Co3O4/TiO2 catalyst was prepared by using hydrothermal method and then was promoted with zirconia by impregnation to get 8% wt. ZrO2-Co3O4/TiO2 catalyst. Catalysts were characterized by using XRD, SEM, and TGA. Catalysts real time activity was tested by coating them on stainless steel wire meshes, containing them in a mild steel shell and mounting them at the exhaust tailpipe of a 72 cm3 motorcycle engine. Zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The XRD patterns of the monometallic sample showed peaks located at 2θ = 9.3, 10.2, 11.6, 12.8, 16.8, 18.2, 19.4, 20.3, 22.7, 29.3, 33.5, and 41.6°, which are in good agreement with the XRD patterns of pure Fe–MOF. , On the other hand, the XRD patterns of bimetallic Co x –Fe 1– x –MOF showed similar diffraction peaks to Fe–MOF. In addition, new diffraction peaks were detected at 2θ = 9.7, 14.1, 15.8, 20.4, and 21.7° reflecting to Co–MOF. , However, new peaks were observed at 19.4, 44.4, and 69.1° with increasing cobalt content to Co 0.75 –Fe 0.25 –MOF, indicating the aggregation of cobalt oxide crystals on the surface of the sample. , Also, the positions of some peaks were changed with changed molar ratios of Co and Fe ions, especially the peak located at 10.2°, indicating the mutual effect of combination between Fe and Co ions with the linker . It is worth noting that the intensity of peaks at 9.3, 9.8, and 10.2° increased after the addition of Co ions (Figure ).…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The XRD patterns of the monometallic sample showed peaks located at 2θ = 9.3, 10.2, 11.6, 12.8, 16.8, 18.2, 19.4, 20.3, 22.7, 29.3, 33.5, and 41.6°, which are in good agreement with the XRD patterns of pure Fe–MOF. , On the other hand, the XRD patterns of bimetallic Co x –Fe 1– x –MOF showed similar diffraction peaks to Fe–MOF. In addition, new diffraction peaks were detected at 2θ = 9.7, 14.1, 15.8, 20.4, and 21.7° reflecting to Co–MOF. , However, new peaks were observed at 19.4, 44.4, and 69.1° with increasing cobalt content to Co 0.75 –Fe 0.25 –MOF, indicating the aggregation of cobalt oxide crystals on the surface of the sample. , Also, the positions of some peaks were changed with changed molar ratios of Co and Fe ions, especially the peak located at 10.2°, indicating the mutual effect of combination between Fe and Co ions with the linker . It is worth noting that the intensity of peaks at 9.3, 9.8, and 10.2° increased after the addition of Co ions (Figure ).…”
Section: Results and Discussionmentioning
confidence: 96%
“…m is the sample weight (g) and V (L) is the solution volume. 44,45 Also, the positions of some peaks were changed with changed molar ratios of Co and Fe ions, especially the peak located at 10.2°, indicating the mutual effect of combination between Fe and Co ions with the linker. 13 It is worth noting that the intensity of peaks at 9.3, 9.8, and 10.2°increased after the addition of Co ions (Figure 1).…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…The slightly lower efficiency of zirconia-promoted catalyst towards HCs is due to the nonavailability of the vacancies of oxygen for oxidation on Co 3 O 4 . Both catalysts showed selectivity towards CO, NO x , and HC, and had comparable performance with respect to the activity of a conventional catalyst [18].…”
Section: The Contents Of the Special Issuementioning
confidence: 92%
“…4 Hence, it has been widely applied in all sorts of applications such as sewage treatment, gas purification, and environmental protection. 3,5,6 There are four natural polymorphs of TiO 2 , namely, anatase (tetragonal), rutile (tetragonal), brookite (orthorhombic), and TiO 2 (monoclinic), 7 of which rutile is more stable than others while three other forms are metastable. 6 It also confirmed that anatase TiO 2 has higher photocatalytic activity than rutile TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is considered to be the most efficient and environmental-friendly photocatalyst because of its particular combination of low budget, chemical stability, nonpoisonous, high reactivity, favorable stability against photocorrosion, and further amelioration of functionalization . Hence, it has been widely applied in all sorts of applications such as sewage treatment, gas purification, and environmental protection. ,, There are four natural polymorphs of TiO 2 , namely, anatase (tetragonal), rutile (tetragonal), brookite (orthorhombic), and TiO 2 (monoclinic), of which rutile is more stable than others while three other forms are metastable . It also confirmed that anatase TiO 2 has higher photocatalytic activity than rutile TiO 2 . , When irradiated with UV light, TiO 2 shows strong oxidation property and reducing capacity.…”
Section: Introductionmentioning
confidence: 99%